A guide to reflective practice for new and experienced teachers - Hartman, Hope J. (McGraw-Hill Higher Education, 2010)
In response to concerns about teacher retention, especially among teachers in their first to fourth year in the classroom, we offer future teachers a series of brief guides full of practical advice that they can refer to in both their student teaching and in their first years on the job. A Guide to Reflective Practice for New and Experienced Teachers is designed to promote reflective practice in both your teaching and in your students’ learning. It is based on current theory and research on how people learn and how to teach in ways that maximize learning. The diverse strategies included are geared towards the needs of new as well as experienced teachers.